Letramento literário no ensino médio: sobre a relação entre literatura e artes visuais em contos de Machado de Assis - Franco, Isaquia dos Santos Barros (Universidade Federal do Tocantins, 2016)
In this paper, we present a propose of literary literacy, based on the relation between literature and visual arts in tales of Machado de Assis. This research is in action research methodology, because it represents a search of a way which leads high school students to the reading of literature texts. For conclusion of this study, first, we do a bibliography review to search an approach and theoretical basic about the proposed theme, with the focus on: literacy and literary literacy; a relation between literature and visual arts and the presence of plastic arts in works of Machado de Assis, targeting the look more specifically to the visuality in three tales of the author. Therefore, we base on the authors as Street (1984), Kleiman (1995), Cosson (2001), Pauline (2009), Lerner (2002), Smith (2011), Praz (1982), Horace (2005), Gonçalves ( 1994 and 1997), Mello (2004), Lessing (1998), Pound (2006), Magellan (1997), Remak (1994), Eulalio (2012), Bastide (2006), Oliveira (2001), Pereira (1973), Sträter (2009), among others. The second moment of this research constituted a field research, which it investigated the reader profile of students, participating of this research. Then, we develop a propose of teaching and learning by literary reading workshops with students of high school at a public school in Grajaú, Maranhão. In this part of the work in are guided by the principles presented by Thiollent (2011), Barbier (2007), Ludke and Andrew (1996). With the results, we understand the work with tales substantiated in visual arts can constitute as a practice of literary literacy at school.